2014
DOI: 10.1097/id.0000000000000181
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up Study of Dental Implants With Bioactive Oxide Films on Bone Tissue Healing and Osseointegration

Abstract: The results confirmed that functional films could improve the biomechanical properties of the implants and promote the initial bone stability. Furthermore, potential clinical benefit can be obtained due to the inducing superior biomechanical behavior in dental implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…A previous study demonstrated that a SLAffinity specimen had an obviously thicker oxide layer (~500 nm) on the surface. The specific surface characteristics of a SLAffinity specimen improved wettability and promoted cell proliferation, adhesion, and spreading [ 14 , 17 ]. In the present study, the SLAffinity group presented a larger area of the bone-screw interface, as well as more osteogenic cells and new bone formation at the peri-implant tissue, which may result from the superior surface properties of this implant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study demonstrated that a SLAffinity specimen had an obviously thicker oxide layer (~500 nm) on the surface. The specific surface characteristics of a SLAffinity specimen improved wettability and promoted cell proliferation, adhesion, and spreading [ 14 , 17 ]. In the present study, the SLAffinity group presented a larger area of the bone-screw interface, as well as more osteogenic cells and new bone formation at the peri-implant tissue, which may result from the superior surface properties of this implant.…”
Section: Discussionmentioning
confidence: 99%
“…We previously applied a novel surface modification called SLAffinity to dental implants. With grit-blasted and acid-etched treated by electrochemical functionalization, a SLAffinity-Ti surface had a 500-nm oxide layer deep inside the Ti structure [ 14 ]. This structure showed high biocompatibility and wettability, allowing ready adhesion to blood.…”
Section: Introductionmentioning
confidence: 99%